The Superior Ability of Human BDCA3+ (CD141+) Dendritic Cells (DCs) to Cross-Present Antigens Derived From Necrotic Lung Cancer Cells - Gu, Fei-fei; Zhang, Kai; Ma, Li-li; Liu, Yang-yang; Li, Chang; Hu, Yue; Yang, Qi-fan; Liang, Jin-yan; Zeng, Yu-lan; Wang, Yan; Liu, Li (Frontiers in Immunology, 2020)
Dendritic cells (DCs) play a key role in initiating and regulating the immune responses to pathogens, self-antigens, and cancers. Human blood DCs comprise a family of different subsets: plasmacytoid DCs (pDCs) and CD16+, CD1c/BDCA1+ and BDCA3+ (CD141+) myeloid DCs and possess different phenotypes and functional characteristics. Lung cancer is the most common cancer, with the highest morbidity and mortality in the world. However, which DC subset plays a leading role in the lung cancer immune responses is unclear. We reanalyzed C-type lectin domain family 9 member A (CLEC9A) and CD141 (THBD) gene expression profiles from the Cancer Genome Atlas (TCGA) database and performed the Kaplan-Meier survival analysis of overall survival for several cancers according to their expression levels. Next, we investigated the capacities of five human blood DC subsets to stimulate T cell proliferation and capture, process and (cross-) present tumor antigen. Human BDCA3+ (CD141+) DCs have a superior capacity to stimulate allogeneic CD4+T cells proliferation and induce superior Th1 response compared with other DC subsets. Interestingly, toll-like receptor (TLR) agonists have little effect on DCs to induce the proliferation of naïve CD4+ T cells, but contribute to their differentiation. Importantly, BDCA3+ (CD141+) DCs possess the most potent ability to cross-present human tumor antigen after their uptake of necrotic lung cancer cells despite their lower antigen uptake. These findings suggest that human BDCA3+ (CD141+) DCs are critical mediators of cytotoxic T lymphocyte responses against EGFR-positive lung cancer. Therefore, our findings may provide theoretical basis for the development of DC-based antitumor vaccines.